Interpretando al describir: la arqueología y las categorías del espacio aborigen en el valle de Santa Maria (noroeste argentino) - Nastri, Javier (Revista Española de Antropología Americana, 2001)
In present work it is analyzed the way archaeologists have defined sectors for late prehispanic settlements of the Santa María valley, in order to expose the complex rclationships between archaeological description and interpretation. Survey of extensive sites located in mountainous topographies and with great quantity of architectural structures requires ways of classification that in most cases could not be planned in advance to the «discovery», nor was it simple after which to modify it, at the risk of introducing confusion on records already made. It is argued that many of the operative decisions related with description of sites have deep implications for general interpretation of late prehispanic period of Argentinean northwest, and for that reason it is indispensable to discuss the underlying hypothesis to each one of the employed units of spatial analysis.